The academic executive handbook on higher education administration - Ables, Higino A. (SEAMEO Regional Center for Graduate Study and Research in Agriculture, 1996)
"This handbook is principally designed for administrators who did not have formal training in academic administration. It most suited for new and aspiring college administrators from department chairmen to college deans to directors of instruction, academic vice-presidents, chief executive officers of colleges and universities or any academic administrators at any level whose office is responsible for managing some aspects of the academic program. University academic affairs coordinators may also find the book useful as they look for ways to improve instructional programs and general management. This publication is dedicated to improving the quality of academic administration in higher education and by consequence the quality of the academic institution."